Sustaining Growth Accelerations and Pro-Poor Growth in Africa - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2005)
Are improvements in growth in Sub-Saharan Africa (SSA) since the mid-1990s sustainable? What types of growth strategies contribute the most to reducing poverty? This paper examines these questions in four stages. First, it explores the factors contributing to the post- 1995 improvement in growth. Second, to shed some light on factors associated with substantial jumps in growth rates that are sustained in the medium term, an analysis of the correlates of growth accelerations is presented. Third, the paper examines the consistency of the SSA data with some important predictions from the literature directly linking such areas as fiscal policy, financial development, or institutions and growth. Fourth, it reviews recent evidence regarding lessons on the type of growth process that is most effective at raising the incomes of the poor.